External and Internal Qualities of Chicken Eggs Early Production at Various Storage Times at Room Temperature - Aju Krisnaningsih; Henny Leondro; Fabiana Lija; Alfindo Agung Setiawan (Faculty of Animal Science Universitas Brawijaya, 2023)
Eggs are one of the consumed foods that contain many essential amino acid nutrients such as lysine, tryptophan, and methionine. Egg quality can be seen from the storability of eggs after they are produced. This study aims to evaluate the effect of various storage lengths on the external and internal quality of chicken egg consumption of the Isa Brown strain at the beginning of production at room temperature. The research method is a Laboratories experiment using a Complete Randomized Design. The study treatment consisted of egg storage duration for 0 days (P0), 7 days (P1), 14 days (P2), and 21 days (P3) with 4 repeats and each test unit of 4 eggs. The research variables include external qualities: egg weight, egg index, shell weight, and eggshell thickness, then internal qualities: egg white index, yolk index, yolk color, and egg pH. The data obtained in this study were analyzed with ANOVA, if there are differences between treatments, then proceed with the the Least Significant Differenttest. The results showed that the duration of deviation had a very noticeable influence (P<0.01) on the external quality of the egg including:egg weight, weightand thickness of the eggshell, and no influence (P>0.01) on the egg index. The length of storage also has a very noticeable influence on the internal quality of eggs (P<0.01). Based on the results of the study, it can be concluded that the initial chicken eggs of production at a storage duration of up to 21 days at room temperature experience a decrease in external and internal qualities but still meet the Standards National Indonesia 3926:2008